1974
DOI: 10.1677/joe.0.0620153
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Oestrogen in the Brain and the Induction of Ovulation in the Guinea-Pig

Abstract: In the guinea-pig, when bilateral oestrogen implants were placed in the medial basal hypothalamus, anterior hypothalamus or suprachiasmatic area on day 10 of the oestrous cycle, ovarian changes indicative of gonadotrophin secretion were observed on day 15. Similarly located cholesterol implants and oestrogen implants outside this region were without effect. The gonadotrophin release was likely to have been induced by an action of the steroid at the hypothalamic, rather than the pituitary level, since bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The change in responsiveness of the gonadotrophic system involves the development of characteristics which permit progesterone to act in a positive feedback fashion. There is reason to think that ovarian oestrogens are responsible for inducing the development of the change which occurs in these tissues in guinea-pigs as in rats (Brown-Grant, 1969;Kalra, Kalra, Krulich, Fawcett & McCann, 1972), notwithstanding the fact that oestrogens also directly stimulate production of gonadotrophins (Booth & Donovan, 1974). Donovan & Lockhart (1972 b) have shown that 2-5 mg progesterone given on day 13 of the cycle are ineffective in inducing ovulation, and their results are in agreement with the present findings.…”
Section: Discussionsupporting
confidence: 90%
“…The change in responsiveness of the gonadotrophic system involves the development of characteristics which permit progesterone to act in a positive feedback fashion. There is reason to think that ovarian oestrogens are responsible for inducing the development of the change which occurs in these tissues in guinea-pigs as in rats (Brown-Grant, 1969;Kalra, Kalra, Krulich, Fawcett & McCann, 1972), notwithstanding the fact that oestrogens also directly stimulate production of gonadotrophins (Booth & Donovan, 1974). Donovan & Lockhart (1972 b) have shown that 2-5 mg progesterone given on day 13 of the cycle are ineffective in inducing ovulation, and their results are in agreement with the present findings.…”
Section: Discussionsupporting
confidence: 90%
“…Again it may be suggested that the steroid hormone acted at a neural level in depressing gonadotrophin secretion and was possibly affecting both facilitatory and inhibitory processes. The direct application of oestrogen to the hypothalamus of intact guinea-pigs has been shown to induce ovulation, and an initial excitation and subsequent inhibition of ovulatory gonadotrophin considered to have taken place, although the tonic secretion of gonadotrophin was unaffected (Booth & Donovan, 1974b). The duration of the LH surge associated with spontaneous ovulation is of the order of 4 hr and peak plasma concentrations of LH between 10 and 30 ng/ml.…”
Section: Hypothalamus and Gonadotrophin Secretion 611mentioning
confidence: 99%
“…Other work (Blatchley et al 1976) has underlined the difficulty of predicting the time of ovulation in guinea-pigs, and it seems that, as in the monkey (Pohl & Knobil, 1982), acute changes in ovarian steroid output serve as the trigger for this event. Gonadotrophin secretion followed the implantation of oestradiol into the hypothalamus of female guinea-pigs (Booth & Donovan, 1974b).…”
Section: Discussionmentioning
confidence: 99%